Membrane Topology of Subunit 8 Variant of Yeast Saccharomyces cerevisiae Mitochondrial ATP Synthase - I MADE ARTIKA (Indonesian Society for microbiology, 2009)
The yeast mitochondrial F1F0-ATP synthase is a multisubunit complex that contains at least 17 different subunits. Subunit 8 of yeast mitochondrial ATP synthase is a hydrophobic protein of 48 amino acids encoded by the mitochondrial ATP8 gene. There is no homologue of subunit 8 found in bacteria. Subunit 8 has three distinct domains; an N-terminal domain, a central hydrophobic domain and a C-terminal domain. Subunit 8 has been shown to adopt a transmembrane topology with the central hydrophobic domain spans the inner mitochondrial membrane once. In order to elucidate the need of subunit 8 to maintain transmembrane topology for its functioning, a severely functionally defective subunit 8 variant that has been introduced with double-charged residues within the central hydrophobic domain was analysed. A gene encoding this variant was expressed in a yeast strain lacking endogenous subunit 8. The subunit 8 variant was then targeted into mitochondria. Following its assembly into mitochondrial ATP synthase complex, its membrane topology was determined. The results obtained showed that subunit 8 was obligatory to maintain a transmembrane topology for providing proper functioning. The transmembrane topology may be critical for subunit 8’s proposed tructural roles as part of the stator stalk of the mitochondrial ATP synthase complex.